Rodinný dům - Homolka, Václav (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Bakalářská práce obsahuje návrh stavebního řešení rodinného domu s provozovnou, který je zpracován ve stupni dokumentace pro provádění stavby. Objekt je situován do města Přeštice na jižním Plzeňsku, má obdélníkový půdorys, dvě nadzemní podlaží a sedlovou střechu. Rodinný dům je přístupný z přilehlé ulice vjezdem a komunikací pro pěší. Objekt je určen pro bydlení i provoz veterinární ordinace majitele domu.

Bachelor thesis includes proposal of the building solution of the detached house with an premises, which is processed in the stage of documentation for construction. The building is situated in the city Přeštice, which is located south of Pilsen. It has a rectangular platform, two floors and a gable roof. The house is accessible to the entrance from the adjacent street and to pavement. The building is designed for the habitation and operation of veterinary medicine by homeowner.
Family house
Keywords: Rodinný dům; obytná část; provozovna; studie; dokumentace pro provádění stavby; Family house; living part; premises; study project; documentation for construction